Melittin induces in vitro death of Leishmania (Leishmania) infantum by triggering the cellular innate immune response. Issue 1 (December 2016) - Pereira, Andreia; de Barros, Gustavo; Pinto, Erika; Tempone, Andre; Orsi, Ricardo de Oliveira; dos Santos, Lucilene; Calvi, Sueli; Ferreira, Rui; Pimenta, Daniel; Barraviera, Benedito
Abstract Background Apis mellifera venom, which has already been recommended as an alternative anti-inflammatory treatment, may be also considered an important source of candidate molecules for biotechnological and biomedical uses, such as the treatment of parasitic diseases. Methods Africanized honeybee venom fromApis mellifera was fractionated by RP-C18-HPLC and the obtained melittin was incubated with promastigotes and intracellular amastigotes ofLeishmania (L.) infantum. Cytotoxicity to mice peritoneal macrophages was evaluated through mitochondrial oxidative activity. The production of anti- and pro-inflammatory cytokines, NO and H2 O2 by macrophages was determined. Results Promastigotes and intracellular amastigotes were susceptible to melittin (IC50 28.3 μg.mL−1 and 1.4 μg.mL−1, respectively), but also showed mammalian cell cytotoxicity with an IC50 value of 5.7 μg.mL−1 . Uninfected macrophages treated with melittin increased the production of IL-10, TNF-α, NO and H2 O2 . Infected melittin-treated macrophages increased IL-12 production, but decreased the levels of IL-10, TNF-α, NO and H2 O2 . Conclusions The results showed that melittin acts in vitro against promastigotes and intracellular amastigotes ofLeishmania (L.) infantum . Furthermore, they can act indirectly on intracellular amastigotes through a macrophage immunomodulatory effect.